PELATIHAN PEMBUATAN HERBARIUM TERHADAP PENINGKATAN KREATIVITAS BELAJAR SISWA - Nur Fitriana Sam (Biopedagogia, 2021)
This study aims to see the level of creativity of students before training and after training in making herbarium and determine the increase in student creativity after training in making herbarium. This study uses a quantitative approach. The type of research is quasi-experimental with a pre-test-post-test design. This research was conducted in January 2015 in Class X IPA MAN Bulungan, North Kalimantan Province, which consisted of 21 students. The instrument used is a questionnaire with a creativity scale that adopts the creativity scale of Utami Munandar and an observation sheet. The data were then analyzed using descriptive analysis techniques and inferential statistics. The study results showed that students' level of learning creativity during the initial test (Pre-test) was relatively high, with an average value of 63.14. Students' level of creativity after the training was classified as very high, with an average value of 85.86. There was a significant increase in student learning creativity after training in making herbarium. Keywords:  Training, Herbarium, Creativity.